Dataset Analysis of Pandemic Risks and Risk Management Prospects Based on Management and Marketing in Conditions of COVID-19 Recession - Anastasiya A. Sozinova; Elena G. Popkova (Risks, 2023)
The motivation for the research was the suddenness of the COVID-19 pandemic and the unavailability of health measures (well-established treatment and vaccination) at the beginning of 2020, which caused an uncontrollable increase in the incidence of disease worldwide and high mortality. The research aims to conduct a dataset analysis of pandemic risks and risk management perspectives based on management and marketing during the COVID-19 recession. The dataset aggregated the statistics on management, marketing, and morbidity during COVID-19 for most countries worldwide that provide data for international statistics (141 countries). Using the developed methodological approach, the authors evaluate the contribution of management and marketing in the fight against the viral threat. The authors calculated specific indices that reflect the contribution of each management and marketing factor separately to combat the viral threat in the second and third trimesters of 2020. The novelty of this research lies in the fact that the dataset study provides a systemic coverage of international experience and develops a universal economic approach to pandemic risk management. The theoretical significance of the research findings is that they reveal differences in the capabilities of economic risk management of a pandemic as the viral threat changes. The practical significance of the research lies in the fact that the results obtained in the third trimester of 2020 make it possible to adjust the policy of the state and corporate risk management of the COVID-19 pandemic during the subsequent pandemic waves, in the post-pandemic period, and in future epidemics and pandemics. Economic measures fill the existing gap, making up for the lack of risk management measures in the early phases of the COVID-19 pandemic.